Lucid dreaming in children: the UK library study - Schredl, Michael; Henley-Einion, Josie; Blagrove, Mark (International journal of dream research, 2012)
The term lucid dream designates a dream in which the dreamer, while dreaming, is aware he or she is dreaming. Whereas lucid dreaming has been studied in adults, large-scaled surveys in children are scarce. The sample here included 3579 children for the ages from 6 to 18 who completed a brief questionnaire distributed in UK libraries. 43.5% reported having had at least one lucid dream. As hypothesized, incidence of lucid dreams was most strongly associated with the preference for reading fantasy/science-fiction. Whether lucid dreaming might be beneficial for children in skills training or coping with nightmares are interesting topics for future research.